EFFECT OF MILK AND EXERCISE IN CHILDHOOD OBESITY: PROTEIN METABOLISM, CARDIOVASCULAR HEALTH AND INFLAMMATION - Gillis, Linda (My University, 2015)
The aim of this thesis was to determine the synergistic effect of milk and exercise to: promote fat loss while maintaining protein balance and muscle; improve cardiovascular fitness and strength; and to evaluate the short-term adaptations of the inflammatory system and metabolic risk factors in overweight adolescents (boys ages 11-15 years, girls ages 9 to 13 years). A 7-day dietary intervention with 1-h intense exercise was used with randomization to milk (MILK: n=26, 8 male, 18 female) or carbohydrate beverage (CONT; n=29, 12 male, 17 female) post exercise. Both groups received a diet based on their resting energy expenditure. To determine whole body protein balance (WBPB), participants consumed 15N-glycine. Subjects performed a maximal cycling test to determine changes in power and 1-repetition maximum testing to determine changes in strength. Blood was taken to evaluate glucose and insulin; tumour necrosis factor-alpha (TNF-α), interleukin-6 and c-reactive protein ; and blood pressure was measured pre and post intervention. Although body weights did not change, the MILK group maintained more muscle (-0.2 ± 0.6 vs. -0.7 ± 0.8 kg, p<0.01) and had a greater loss in body fat (-0.4 ± 1 vs. 0.5 ± 1.0 %, p<0.006). The changes in body composition were supported by a greater WBPB after training in the MILK group (1.64 ± 1.1 vs. 0.84 ± 0.6, p<0.001). Power increased only in the MILK group with an increase of 0.13 watts/kg (p<0.05) with an increase in V02max that approached significance (p=0.06). Improvements in strength and the blood risk factors were not different between the groups. There was a greater decline in mean arterial pressure in the MILK group (-3 ± 6 mmHg vs. 2 ± 7 mmHg, p< 0.04). The exercise intervention led to an increase in TNF-α in both groups (0.3 ± 0.7 pg/ml vs. 0.5 ± 0.7 pg/ml, p<0.001). These data support the consumption of milk after exercise in the early stages of pediatric obesity treatment.
Keywords: pediatric obesity, milk, exercise